From Clicks to Carts: Examining the Mediating Role of Attachment in the Relationship Between Influencers and Consumer Purchase Intentions on Live Streaming Platforms - Rui, Wang; Mohamad, Bahtiar (Journal of Ecohumanism, 2024)
Internet celebrities are rapidly reshaping economics and marketing dynamics on online platforms such as live streaming. This trend has made influencers a crucial marketing technique for many businesses. This study focuses on influencers and their characteristics, engaging in a comprehensive discussion of their complex relationships. It hypothesizes that the three key characteristics of celebrity influencers—similarity, professionalism, and interactivity—directly influence attachment and purchase intention. Additionally, the research explores how attachment mediates the relationship between influencer factors and purchase intention on live streaming platforms. A cross-sectional design and statistical analysis were employed, using a sample of 130 online consumers. The results suggest that similarity, professionalism, and interactivity directly effect on purchase intention. However, while professionalism and interactivity have a direct effect on attachment, they do not significantly influence the relationship with similarity. However, when mediated through attachment, similarity gets partially mediated whereas professionalism and interactivity have observed full mediation. The total effect is highest for similarity. Overall, the study found attachment to be a significant mediator among these influencer characteristics. These findings suggest that celebrities, product developers, advertisers, and online platform owners need to prioritize influencer credibility and competency to succeed in online marketing through live streaming platforms. This study provides new insights into marketing approaches, contributing to the field of consumer behaviour research both practically and theoretically.